2010
DOI: 10.1001/archinternmed.2010.65
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interruptions With an Increased Risk and Severity of Medication Administration Errors

Abstract: Among nurses at 2 hospitals, the occurrence and frequency of interruptions were significantly associated with the incidence of procedural failures and clinical errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
531
6
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(594 citation statements)
references
References 35 publications
27
531
6
14
Order By: Relevance
“…The error severity, which is 2.3% in the absence of interruption, becomes 4.7% in the presence of four interruptions (3). Our results support the results of Westbrook et al (3). This result is also important as it sets a guide for planning the interventions aiming at preventing interruptions as study results on the ratios and reasons of medication errors made by nurses are utterly limited in the literature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The error severity, which is 2.3% in the absence of interruption, becomes 4.7% in the presence of four interruptions (3). Our results support the results of Westbrook et al (3). This result is also important as it sets a guide for planning the interventions aiming at preventing interruptions as study results on the ratios and reasons of medication errors made by nurses are utterly limited in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Biron et al (5), nurses experienced interruption for at least once in more than half of the medications they prepared. In the study of Westbrook et al (3), the ratio of interruptions experienced during the stage of medication administration was reported as 53.1%. In the interventional study of Pape (11), which aimed at preventing interruptions during the medication preparation, the control group experienced 484 interruptions while the group where interventions were applied to prevent interruptions experienced 64 interruptions.…”
Section: Discussionmentioning
confidence: 95%
“…Este cenário é incoerente ao recomendado, que deveria ser um ambiente seja reservado, com fluxo restrito de pessoas, tranquilo e sem fonte de interrupção ou distração, como televisão e/ou rádio (17) . Em um estudo realizado em dois hospitais na Austrália, verificou-se que o aumento do número de interrupções foi ligado ao aumento das taxas de erro (18) . Entre os fatores que provocam distrações durante as tarefas de trabalho dos profissionais de enfermagem estão: ausência de planejamento formal da assistência de enfermagem, telefone celular e/ou institucional tocando, sobreposição de diferentes tarefas, mudanças não padronizadas de prescrição médica e interrupções geradas por outros profissionais (19) .…”
Section: Discussionunclassified
“…6 A study conducted by Johanna I. Westbrook at 2010 suggests the administering errors to the patient as 74.4%. In this study, the administering and dispensing errors were found to be 53.24%.…”
Section: Discussionmentioning
confidence: 99%